2019
DOI: 10.3390/su11164276
|View full text |Cite
|
Sign up to set email alerts
|

Housing Indicators for Sustainable Cities in Middle-Income Countries through the Residential Urban Environment Recognized Using Single-Family Housing Rating Systems

Abstract: This study presents a comparative analysis of the housing indicators used by the singlefamilyhousing rating systems (SHRSs), in which the residential urban environment (RUE)influences buildings’ certification scores, emphasizing the relationships of six systems developedby middle‐income countries (MICs)—BEST, CASA, GBI, BERDE, Green Homes, and LOTUS—andthe two most‐recognized rating systems, BREEAM and LEED. The aim is to provide new housingindicators that are capable of bringing the concept of sustainability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…However, it can be observed that the application of certain tools must be in line with the normative and legal context of the place in question. Managers and consultants need to understand the social, economic, and environmental characteristics to follow the most appropriate procedures [20]. References [12,13] points out that methodologies, such as LEED, BREEAM, and SBTool, were initially developed according to the realities of their countries of origin and, then, were adapted to the circumstances of each country in which they were applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it can be observed that the application of certain tools must be in line with the normative and legal context of the place in question. Managers and consultants need to understand the social, economic, and environmental characteristics to follow the most appropriate procedures [20]. References [12,13] points out that methodologies, such as LEED, BREEAM, and SBTool, were initially developed according to the realities of their countries of origin and, then, were adapted to the circumstances of each country in which they were applied.…”
Section: Discussionmentioning
confidence: 99%
“…The studies carried out in Mexico by [13,20] indicate that housing developed by the funding program for housing solutions obtained low qualifications according to building sustainability rating systems, with deficiencies concerning materials, energy efficiency, indoor environmental quality, and management. The authors have also pointed out that Mexican sustainable social housing does not comply with other global certifications among all indicators, as much as we could detect in Brazil, mainly those that depend on urban indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is number of different housing market indicators that help identify the magnitude and nature of housing affordability problems and their geographic distribution. -Márquez et al (2019) presented a comparative analysis of the housing indicators used by the single-family housing rating systems, in which the residential urban environment influences buildings' certification scores, emphasizing the relationships of six systems developed by middle-income countries (MICs) and the two most-recognized rating systems. The aim was to provide new housing indicators that are capable of bringing the concept of sustainability into the cities of MICs.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Method), and GB tool (Green Building Tool) are well-known systems for evaluating the environmental performance of buildings. Comparative studies of these evaluation systems are underway [2,3]. In this, for example, an evaluation factor included in LEED is the use of building materials that quantify GHG emissions based on the life cycle assessment (LCA) method.…”
Section: Background and Purposementioning
confidence: 99%